The population genetics of red squirrels in a fragmented habitat - Todd, Rebecca (2000)
The genetics of eight small red squirrel (Sciurus vulgaris L. ) populations in northern Belgium is investigated by analysing variation in a section of the mitochondrial control region and five microsatellite loci. The full sequence of the mitochondrial control region in red squirrels is determined and is compared to that of other mammals. The isolation of microsatellite loci is also described. The eight fragment populations are compared with two large Belgian populations and one large population in the Bavarian Forest, Germany. Virtually no variation is found in the control region within any of the Belgian squirrels, although the German population is found to be highly variable. However, the Belgian and German samples show comparable levels of diversity at the microsatellite loci. The lack of variation in the control region of the Belgian squirrels suggests that they have lost variation, due to either selective or demographic pressures. A combination of a bottleneck and metapopulation structuring could lead to reduced diversity levels and explain the observed patterns of variation. The recent effects of habitat fragmentation and population expansion can be seen in the microsatellite data. Three of the fragment populations show evidence of recent bottlenecks or founder events, probably due to the recent colonisation of these areas by squirrels from nearby expanding populations. Estimations of FsT and RsT show that there is some differentiation among the populations, but none of the populations are significantly differentiated from any of the others. There is no correlation between genetic differentiation and geographic distance indicating that migration is influenced by other factors as well as distance. The fragment populations all contain more allelic diversity than would be expected in populations of their size at mutation-drift equilibrium. Migration between the populations appears to be maintaining nuclear variation and counteracting the effects of random genetic drift.